Kreatifitas Dalam Periklanan Media Luar Ruang (MLR) Di Kota Medan (Peluang, Tantangan, dan Konsep Pemberdayaan Masyarakat) - Tengku Walisyah (Jurnal Pemberdayaan Masyarakat, 2020)
Abstract: outdoor advertising in Medan City nowadays gets dynamic and attractive design. It indicates that the design established with so unique, uncommon, and different with others that it makes the outdoor advertising becomes creative one. Consequently, this creative value produces opportunities and challenges in a better way, furthermore the appearance of the design requires more creative and innovative.